2017
DOI: 10.1371/journal.pone.0186000
|View full text |Cite
|
Sign up to set email alerts
|

HIV/Human herpesvirus co-infections: Impact on tryptophan-kynurenine pathway and immune reconstitution

Abstract: BackgroundCo-infections with human herpesvirus (HHV) have been associated with residual chronic inflammation in antiretroviral (ART)-treated human immunodeficiency virus (HIV)-infected individuals. However, the role of HHV in modulating the tryptophan-kynurenine pathway and clinical outcomes in HIV-infected individuals is poorly understood. Thus, we investigated the seroprevalence of four common HHVs among treated HIV-infected participants and their impact on kynurenine/tryptophan (K/T) ratio and long-term CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 56 publications
0
23
0
2
Order By: Relevance
“…Immunosuppressed HCMV-infected transplant recipients have elevated KYN serum levels (18). Additionally, people with HCMV and human immunodeficiency virus type 1 (HIV-1) co-infection have enhanced KYN serum levels relative to those with HIV and herpes simplex virus type 1 (HSV-1) co-infection (19). While our observations demonstrate that HCMV-infection increases Figure 5B) (22).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Immunosuppressed HCMV-infected transplant recipients have elevated KYN serum levels (18). Additionally, people with HCMV and human immunodeficiency virus type 1 (HIV-1) co-infection have enhanced KYN serum levels relative to those with HIV and herpes simplex virus type 1 (HSV-1) co-infection (19). While our observations demonstrate that HCMV-infection increases Figure 5B) (22).…”
Section: Discussionmentioning
confidence: 57%
“…Peaks 1 and 4 remain unidentified. Since the levels of KYN in human serum were previously found to be associated with HCMV infection (18,19), we decided to focus on the role of KYN in virus replication.…”
Section: Metabolic Regulation By Hif1α In Hcmv-infected Cellsmentioning
confidence: 99%
“…However, reduced Lactobacillales was not correlated with increased plasma IDO activity in our study (data not shown). The lack of correlation could potentially be explained by the presence of other IDO mediators including IFN-α levels, which we recently showed to remain elevated despite years of suppressive ART in our setting 52 . The association between reduced Lactobacillales and CD4 T-cell counts was also weaker when compared to Fusobacterium in our cohort and was lost when both bacterial taxa were included in a multiple linear regression model.…”
Section: Discussionmentioning
confidence: 74%
“…The Kyn:Trp ratio, measured in blood, is a valuable clinical benchmark of IDO-1 activation, and reflects the state of immune activation or tolerance in cancer immunity, autoimmunity, infection and other disorders. Changes in Kyn:Trp ratio have been associated with viral infections, such as HIV and HIV-human herpes virus co-infection [ 14 ], seasonal influenza [ 15 ], Dengue virus [ 16 ], and HBV [ 17 ].…”
Section: Introductionmentioning
confidence: 99%